Comportamiento de la variedad de rosa (Rosa sp.) Daniela frente a la aplicación de Giberelinas (GA3), bajo invernadero, Guachalá-Cayambe 2011 - Quinchiguango Puma, Nelly Isabel (2012)
The present study was conducted on the Terrafrut farm in the parish of Cangahua at a height of 2800 meters above sea level, and an extension has 40hc and in production vineyards. The objectives were the following: determine the best concentration of Gibberellins to increase the size and diameter of button, determine the most appropriate concentration of Gibberellins to increase the size and diameter of peduncle, evaluate the tonality of the flower buds of the variety, set what concentrations presents durability in a vase.